2015
DOI: 10.1186/s12890-015-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Lung MRI and impairment of diaphragmatic function in Pompe disease

Abstract: BackgroundPompe disease is a progressive metabolic myopathy. Involvement of respiratory muscles leads to progressive pulmonary dysfunction, particularly in supine position. Diaphragmatic weakness is considered to be the most important component. Standard spirometry is to some extent indicative but provides too little insight into diaphragmatic dynamics. We used lung MRI to study diaphragmatic and chest-wall movements in Pompe disease.MethodsIn ten adult Pompe patients and six volunteers, we acquired two static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…While we were completing our observations, Wens et al [22] described the use of lung MRI to evaluate diaphragmatic function in 10 patients with Pompe disease and six volunteers: their results are impressively similar to the data obtained in this study. They found that Pompe patients had smaller craniocaudal movements in comparison with volunteers and that the range of diaphragmatic movements strongly correlated with FVC in supine position and postural drop.…”
Section: Discussionsupporting
confidence: 92%
“…While we were completing our observations, Wens et al [22] described the use of lung MRI to evaluate diaphragmatic function in 10 patients with Pompe disease and six volunteers: their results are impressively similar to the data obtained in this study. They found that Pompe patients had smaller craniocaudal movements in comparison with volunteers and that the range of diaphragmatic movements strongly correlated with FVC in supine position and postural drop.…”
Section: Discussionsupporting
confidence: 92%
“…[37][38][39] For a more detailed evaluation of pulmonary function, spirometrycontrolled MRI or ultrasonography of the diaphragm may be appropriate. [40][41][42] In addition, evaluation of muscle function could possibly be more reliably evaluated with patientreported outcome measures, reporting activities in daily life. 43,44 In 2017, European consensus guidelines were published on the use of ERT in adult patients with Pompe disease.…”
Section: Discussionmentioning
confidence: 99%
“…Over dynamic MRI techniques, static MRI provides higher spatial resolution and reduced scan time, simplifying image analysis and allowing the use of automatic algorithms for 3D lung segmentation and diaphragm reconstruction. The diaphragm kinematics have been previously investigated in neuromuscular disease, by following the 2D temporal profile of the lung cross‐section from a dynamic MRI acquisition or by measuring changes in lung dimensions between inspiration and expiration . The 3D representation of the diaphragm allows a more accurate and robust analysis, with the possibility of tracking and evaluating different regions.…”
Section: Discussionmentioning
confidence: 99%